1999
DOI: 10.1021/jm990104o
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Benzothiazoles. 8. Synthesis, Metabolic Formation, and Biological Properties of the C- and N-Oxidation Products of Antitumor 2-(4-Aminophenyl)benzothiazoles

Abstract: 2-(4-Aminophenyl)benzothiazoles 1 and their N-acetylated forms have been converted to C- and N-hydroxylated derivatives to investigate the role of metabolic oxidation in the mode of action of this series of compounds. 2-(4-Amino-3-methylphenyl)benzothiazole (1a, DF 203, NSC 674495) is a novel and potent antitumor agent with selective growth inhibitory properties against human cancer cell lines. Very low IC(50) values (<0.1 microM) were encountered in the most sensitive breast cancer cell lines, MCF-7 and T-47D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
141
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(145 citation statements)
references
References 16 publications
3
141
0
1
Order By: Relevance
“…Previous observations have shown that cytotoxicity of benzothiazoles is mediated via activation of the AhR signalling pathway (Kashiyama et al, 1999;Chua et al, 2000;Loaiza-Pérez et al, 2002). In addition, cytotoxicity across a large panel of human tumour cell lines correlates with CYP1A1 inducibility .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous observations have shown that cytotoxicity of benzothiazoles is mediated via activation of the AhR signalling pathway (Kashiyama et al, 1999;Chua et al, 2000;Loaiza-Pérez et al, 2002). In addition, cytotoxicity across a large panel of human tumour cell lines correlates with CYP1A1 inducibility .…”
Section: Resultsmentioning
confidence: 95%
“…2-(4-Amino-3-methylphenyl)benzothiazoles are novel compounds with potent and unique antitumour properties (Shi et al, 1996;Bradshaw et al, 1998a, b;Kashiyama et al, 1999). It was demonstrated that selective metabolism in vitro of the parent agent DF 203 (NSC 674495) correlated very highly with its antiproliferative activity, with uptake and biotransformation observed only in those cell lines that are sensitive to the compound, such as MCF-7 and T47D breast carcinoma cells (Kashiyama et al, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Benzothiazole derivatives represent an extensive group of heterocyclic compounds, several of which have already found application in the medical sphere as medicines (Kashiyama et al 1999) as well as in agriculture (Pulkrábek et al 1999, Henselová et al 2001). 3-R-substituted benzothiazole derivatives induced dedifferentiation and morphogenesis of plants in vitro (Sekerka et al 1989), influenced growth in Triticum aestivum (Sutoris et al 1993) and stimulated plant regeneration and peroxidase activity in Brassica oleraceae (Havel et al 1994).…”
mentioning
confidence: 99%
“…We have shown that cells lines inherently sensitive to this class of agent rapidly sequester and metabolize 2-(4-aminophenyl)benzothiazoles, whereas no net uptake was detected by intrinsically resistant cell lines Kashiyama et al 1999). Compared with MCF-7 wt and MCF-7 10 µM 126 , MCF-7 10 nM 126 cells, selected in the presence of the more cytotoxic concentration of 10 nM CJM 126, demonstrated dramatically impaired depletion of CJM 126 from media ( Figure 3A) with predominantly cytoplasmic intracellular drug localization (Figure 4).…”
Section: Discussionmentioning
confidence: 93%